ESTETIKA SINDHENAN KULONAN SURYATI DALAM GENDHING BANYUMASAN - Budiarti, Muriah (Institut Seni Indoensia Surakarta, 2021)
This research is motivated by a unique phenomenon about Sindhenan which has a unique aesthetic, namely Pesindhen Suryati. As a singer, Suryati represents the aesthetic of kulonan (Banyumasan with Pasundan style) especially in gending Banyumasan. The concept of kulonan aesthetics is a new kind of aesthetic which has never been definitively revealed what are the elements that make up the aesthetic. The problems of this research are 1) What is the background of the Suryati’s sindhenan style so that it can represent the kulonan aesthetic? 2) How is the practice of kulonan aesthetics in Suryati’s sindhenan? 3) what are the elements that make up the kulonan aesthetics of Suryati’s sindhenan?This research was conducted qualitatively, with the stages: observation, literature study, interviews, conceptual determination, data analysis, and report writing. To reveal the problems, this study uses the theory of Lono Lastoro SimatupangThe conclusions of this research are 1) the Suryati’s sindhenan of kulonan aesthetics is formed by: bodily experiences influenced by genes, environment and social culture. 2) The constituent elements of Suryati’s kulonan aesthetics are recitation techniques, vocal ornamentation, and musical taste as well as impression.Keyword: Aeshtetics, sindhenan, kulonan, Suryati, Banyumas